Evaluating the Vaccine Potential of a Tetravalent Fusion Protein (rBmHAXT) Vaccine Antigen Against Lymphatic Filariasis in a Mouse Model - Chauhan, Nikhil; Khatri, Vishal; Banerjee, Priyankana; Kalyanasundaram, Ramaswamy (Frontiers in Immunology, 2018)
Lymphatic filariasis (LF) is a tropical parasitic infection of human transmitted by mosquitoes. Chronic infection results in severe physical disability in the infected patients. Although several potential vaccine antigens were identified several groups, there are no licensed prophylactic vaccine to date against this infection in the human. Previous attempts from our laboratory to develop a trivalent prophylactic vaccine against LF showed that >90% protection could be achieved in rodent models. However, this trivalent vaccine gave only 35% protection in non-human primates. The major focus of this study was to develop a tetravalent prophylactic vaccine (rBmHAXT) and test the vaccine potential in a mouse model. We evaluated three different adjuvant formulations; alum, glucopyranosyl lipid adjuvant in stable emulsion (GLA/SE) alum (AL019) and mannosylated chitosan (MCA) to determine the optimum adjuvant formulation for rBmHAXT. Results presented in this study show that rBmHAXT + AL019 gave the highest rate of protection (>88%) against challenge infection, compared to rBmHAXT+AL007 (79%) and rBmHAXT+MCA (79%) compared to controls. Analysis of the immune correlates of protection showed that all three adjuvants elicited high titer of antigen specific IgG1, IgG2a and IgG2b antibodies. High number of IFN-γ producing antigen-specific memory cells were generated in the vaccinated animals irrespective of the adjuvants used. Similarly, spleen cells from rBmHAXT vaccinated animals secreted IL-4, IL-10 and IFN-γ in response to rBmHAXT suggesting the generation of a balanced Th1/Th2 response. There was also an increase in IL-17 secreting cells in rBmHAXT vaccinated animals. These finds thus suggest that that rBmHAXT + AL019 is a better prophylactic formulation for LF.